True Value of Telecentre Contribution to Bario Community Development - Ghazala, Tabassum; Narayanan, Kulathuramaiyer; Harris, Roger W.; Yeo, Alvin Wee (Springer New York LLC, 2017)
Telecentres have been widely deployed worldwide particularly in the area of ICTD to bridge the gap between urban and rural development. This paper explores the value and impact of a telecentre on the community living in Bario, a small village in the highlands of Malaysia. The focus is mainly on the less studied tangible and intangible impacts of the telecentre on users and non-users. This topic is discussed based on stories collected through “Most Significant Change Technique (MSC)” providing facts from the insights of the local community. In nutshell, Bario community has greatly benefited from the use of the telecentre, whether directly or indirectly, particularly in the areas of connectedness, psychological empowerment, and financial improvement. Greater awareness and use of the telecentre shall continue to benefit this small rural community in their social and economic wellbeing.